독도의 조류상 - 김창회(Chang-Hoe Kim); 권영수(Young-Soo Kwon); 강종현(Jong-Hyun Kang); 유정칠(Jeong-Chil Yoo) (한국조류학회지, 2007)
본 조사는 2005-2006년에 경상북도 울릉군 독도에서 실시되었다. 독도에서 관찰된 조류는 126 종으로 조사되었다. 개체수가 가장 많이 관찰된 종은 괭이갈매기(Larus crassirostris)이었고 약7,000개체가 번식하는 것으로 조사되었다. 그리고 바다제비(Oceanodroma monorhi), 슴새(Calonectris leucomelas), 참새(Passer montanus)도 번식하는 것으로 조사되었다. 독도에 도래하는 조류의 대부분은 봄과 가을철에 관찰되었고, 정주성인 조류보다는 이동성 조류가 많았다. This study was conducted during the 2005-2006 in Dokdo Island (Dongdo and Seodo), Ulleung-gun, Kyeongsang-bukdo, Republic of Korea. The birds of 126 species were observed in Dok-do. The Black-tailed Gull (Larus crassirostris) was a dominant species and about 7,000 birds bred in Dongdo (1,500 nests) and Seodo (2,000 nests). The Swinhoe's Fork-taled Petrel (Oceanodroma monorhi), the Streaked Shearwater (Calonectris leucomelas) and the Tree Sparrow (Passer montanus) also bred in there. Most of birds were observed in Spring and Autumn and migratory birds rather than sedentary ones. KCI Citation Count: 4